Swyer Syndrome: Clinical Case of Gonadal Dysgenesis in a 15-year-old Girl - Irina V. Karachentsova; Elena V. Sibirskaya; Tatyana G. Dyadik; Mariia Yu. Chernysheva; Kristina A. Osmanova; Varvara M. Golubkova; Anna V. Arutunyan; Angelina A. Sysoeva (Union of pediatricians of Russia, 2024)
Swyer syndrome is a rare genetic disorder in which gonadal dysgenesis and karyotype 46, XY are observed. In the postnatal and prepubescent period, this disease has no clinical manifestations and is asymptomatic, which makes diagnosis difficult. The first signs of the syndrome appear in puberty in the form of underdevelopment of secondary sexual characteristics. This review presents the criteria based on which such a diagnosis as Swyer syndrome can be made. The main diagnostic methods are highlighted, the possibilities of both surgical treatment of patients and drug treatment due to hormone replacement therapy are considered. Verification of the syndrome contributes to a more thorough examination, which will allow you to determine management tactics and avoid complications from other organs and systems.